2020
DOI: 10.1016/j.rmed.2020.106045
|View full text |Cite
|
Sign up to set email alerts
|

Use of corticosteroids in asthma and COPD patients with or without COVID-19

Abstract: The potential detrimental effects of steroids on the immune system to fight viral infections had always been a concern for patients on long term steroids in chronic conditions. A recent warning from WHO on systemic corticosteroid use amid COVID-19 raised suspicion among public and healthcare professionals regarding the safety of steroid use during the SARS-CoV-2 pandemic. The corticosteroids (inhaled and oral) are commonly prescribed in the management of asthma and COPD patients and any unsolicited changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 48 publications
(46 reference statements)
1
33
0
Order By: Relevance
“…Although recent studies have shown that the use of GC s in the moderate to severe acute phase of COVID-19 has led to a benefit, 20 21 the effect seems to be deleterious in patients on chronic use, probably associated increased risk of infection with higher dose of GC, 22 due to impairment of innate immune responses with a reduction in neutrophil recruitment and a delay in viral clearance. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have shown that the use of GC s in the moderate to severe acute phase of COVID-19 has led to a benefit, 20 21 the effect seems to be deleterious in patients on chronic use, probably associated increased risk of infection with higher dose of GC, 22 due to impairment of innate immune responses with a reduction in neutrophil recruitment and a delay in viral clearance. 23 …”
Section: Discussionmentioning
confidence: 99%
“…In general, both the Global Initiative for Asthma (GINA) and Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines recommend that patients should be maintained on their regular therapy and that no medication should be discontinued ( (GINA) GIfA, 2020 ; (GOLD) GIfCOLD, 2020 ). In patients infected with COVID-19 who have asthma or COPD exacerbations, the usual course of management, including the administration of a short course of oral corticosteroids should be followed but only under the supervision of a physician ( Hasan et al, 2020 ). Lastly, an important point to consider in clinics is the risk of viral transmission via nebulized treatment.…”
Section: The Association Between Covid-19 and The Most Common Chronicmentioning
confidence: 99%
“…Lastly, an important point to consider in clinics is the risk of viral transmission via nebulized treatment. It has been recommended that patients with COVID-19 associated asthma or COPD exacerbation should not be administered bronchodilators or corticosteroids through nebulization, to avoid the risk of infecting other patients and healthcare providers ( Hasan et al, 2020 ). In these cases, metered-dose inhalers are preferred, however if not possible then patients using the nebuliser in their homes or in a clinical setting should take their medication in an isolated room and take the necessary precautions ( Hasan et al, 2020 ).…”
Section: The Association Between Covid-19 and The Most Common Chronicmentioning
confidence: 99%
“…Compared to inhaled corticosteroids coupled with long-acting β2-agonists, dual long-acting bronchodilators may exhibit a more significant reduction of exacerbation frequency, while bearing a lower risk of pneumonia. However, sometimes it may be necessary to continue ICS-including therapy in case of good symptoms control [45].…”
Section: Basic Chronic Obstructive Pulmonary Disease Treatmentmentioning
confidence: 99%
“…Delaying the therapy is not recommended, as severe exacerbations may occur in this time. Short-term use of oral corticosteroids is favourable in the resolution of more severe disease symptoms and can be abandoned suddenly, as the exacerbations vanish [45].…”
Section: Treatment Of Patients With Copd and Covid-19mentioning
confidence: 99%